Exploring requirements for indoor navigation systems - Ni, Chunxiao (2013)
Indoor navigation has been a subject in ubiquitous computing domain in the past decade. Recently many studies focus on exploring user requirements for indoor navigation systems and make effort in developing effective interactive systems to support indoor navigation. This study aims to find which kind of spatial representation and what orientation cues common users prefer to use for indoor navigation. An experiment was performed to examine the navigation effectiveness and user satisfaction with a prototype indoor navigation system. The results reveal there is no accordant preference for a certain spatial representation or orientation cue. And additional orientation cues do not bring improved navigation effectiveness compared with a single static map. More requirements for indoor navigation systems are also found in the study.